(untitled) (The Agriculturists, 2018)
Five Trichoderma species/strains, Trichoderma virens IMI-392430, T. pseudokoningii IMI-392431, T. harzianum IMI-392432, T. harzianum IMI-392433 and T. harzianum IMI-392434 were tested against anthracnose and fruit rot of chilli. Effect of Trichoderma species in suppressing anthracnose and fruit rot as well as the growth and yield of chilli were evaluated. Seven treatments consisting of five Trichoderma strains, one Colletotrichum capsici and control were used as seed treatments. Chilli seeds were treated with spore suspension or secondary metabolites of each Trichoderma species/strain and C. capsici separately. Mixture of suspension of each Trichoderma species/strain with C. capsici was also used as spore suspension or secondary metabolites. Percent fruit infection in the control treatment was found almost similar to the treatment that contained T. viridae and T. pseudokoningii spore suspension or secondary metabolites. T. harzianum strains alone suppressed fruit infection (%) significantly. Further all the Trichoderma species/strains reduced the fruit infection (%) than the diseased control even when seeds were treated with Trichoderma separately mixing with C. capsici. Spore suspension of T. harzianum IMI-392433 was found much more effective against C. capsici which suppressed 95.8% and 79.6 % fruit infection respectively under natural (without C. capsici) and high inoculum pressure of C. capsici. All the tested Trichoderma species/strains showed higher plant growth and increased fruit yield irrespective of rest of the treatments. It was found that Trichoderma strains control chilli fruit rot significantly but high inoculum pressure of C. capsici reduced fruit yield drastically. Among the treatments, spore suspension of T. harzianum IMI-392433 increased the fruit yield 83.6% and 76.5% per plant compared to spore suspension of C. capsici and control treatments, respectively. These results implied that T. harzianum IMI-392433 can effectively control fruit rot of chili caused by C. capsici through host resistance and antifungal metabolite activity. The fruit yield was increased due to the influence of T. harzianum IMI-392433 on vigorous physiological growth of plants as well as efficacy against the disease. The Agriculturists 2018; 16(2) 75-87